2015
DOI: 10.17306/j.afs.2015.4.30
|View full text |Cite
|
Sign up to set email alerts
|

Application of acid whey and set milk to marinate beef with reference to quality parameters and product safety

Abstract: Background. The aim of the study was to evaluate the potential of acid whey and set milk as a marinade in the traditional production of fermented eye round. Material and methods. Studies involved assaying pH value, water activity (a w ), oxidation-reduction potential and TBARS value, colour parameters in CIE system (L*, a*, b*), assaying the number of lactic acid bacteria and certain pathogenic bacteria after ripening process and after 60-day storing in cold storage. Sensory analysis and analysis of the fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 15 publications
7
22
0
1
Order By: Relevance
“…It was shown that marinating chicken muscles using whey significantly (p <0.05) increased the number of lactic acid bacteria compared with the control and marinating using lemon juice (Table 3). Similar results were obtained by Wójciak et al (2014) and Wójciak et al (2015) in a pork and beef product marinated in whey with the addition of sea salt. According to Wójciak et al (2014), an addition of sea salt contributes to the growth of lactic acid bacteria in a meat product marinated with whey.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…It was shown that marinating chicken muscles using whey significantly (p <0.05) increased the number of lactic acid bacteria compared with the control and marinating using lemon juice (Table 3). Similar results were obtained by Wójciak et al (2014) and Wójciak et al (2015) in a pork and beef product marinated in whey with the addition of sea salt. According to Wójciak et al (2014), an addition of sea salt contributes to the growth of lactic acid bacteria in a meat product marinated with whey.…”
Section: Resultssupporting
confidence: 83%
“…Meat tenderness is one of the most important charracteristics determining quality and consumer acceptance. Many studies (Ergezer and Gokce, 2011;Ke et al 2009, Kim 2018, Kumar et al, 2017Serdaroğlu et al, 2006;Wójciak et al, 2015) have indicated that the low meat pH after marination has positive effects on the texture. The present study indicated a significant (p <0.05) effect of the applied marinating additives on the tenderness of both raw breast muscles and those subjected to heat treatment (Table 1 and Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in marinade absorption could be due to the density of marinades, differences in the osmotic pressure exerted by different marinade solutions, and also the marinades' pH. Many authors [8,14,16,34,35] indicate that the acidity of marinated meat depends on the pH of the marinade, as confirmed in the present study. e pH value of raw pheasant breast muscles marinated with acid whey and buttermilk was significantly (p < 0.05) lower than that of those marinated with lemon juice.…”
Section: Resultssupporting
confidence: 82%
“…By-products of the dairy industry, such as whey and buttermilk, are currently used in the production of functional foods and enjoy the interest of the meat industry and consumers in households. e results of the latest scientific research indicate the possibility of using acid whey for marinating beef and pork [12][13][14][15][16][17][18] to improve the sensory characteristics and tenderness and inhibit oxidative changes in the meat products. Vlahova-Vangelova et al [19] showed the beneficial effect of marinating on organoleptic characteristics (smell and consistency) of broiler chicken meat.…”
Section: Introductionmentioning
confidence: 99%